THE EFFECT OF FOOT EXERCISE ON THE STATUS OF LOWER EXTREMITY SENSORY NEUROPATHY IN PATIENTS WITH TYPE 2 DIABETES MELLITUS AT THE TANJUNGANOM HEALTH CENTER, NGANJUK REGENCY - Leili Setiawan Rosyid Leili Setiawan Rosyid (Indonesian Journal of Community Health Nursing, 2023)
The increasing prevalence of type 2 Diabetes Mellitus in both developed and developing countries so that it becomes a health problem or a global disease in society. Therefore type 2 Diabetes Mellitus can be prevented by regular exercise, healthy and regular living. The purpose of this study was to determine the effect of foot exercise on the status of lower limb sensory neuropathy in patients with type 2 diabetes mellitus at the Tanjunganom Health Center, Nganjuk Regency. The design in this study was pre-experimental with a one-group pre-posttest design approach. This research looked for the effect of foot exercise on lower limb sensory neuropathy status in patients with type 2 diabetes mellitus at the Tanjunganom Health Center, Nganjuk Regency, in this study involved 30 respondents using a purposive sampling technique. sampling. This research was conducted on 14 – 21 October 2022. From the results of the Wilcoxon test, the results obtained after foot exercise were the status of lower limb sensory neuropathy in the right limb, ρ value = 0.000 ≤ α 0.05, this indicated that there was an effect of foot exercise on lower limb sensory neuropathy status in patients with type 2 diabetes mellitus at the Puskesmas. Tanjunganom, Nganjuk Regency. In this study it was found that there was an effect of foot exercise on the status of lower extremity sensory neuropathy in patients with type 2 diabetes mellitus. Keywords: Foot Exercise, Lower Extremity Sensory Neuropathy, Diabetes Mellitus.